Setting parametric limits on dialectal variation in Spanish - Toribio, Almeida Jacqueline (Lingua, 2000)
The present investigation departs from the perspective that dialects of languages may exemplify typological distinctions, and as such, may be defined within parametric limits. More specifically, this synchronic study focuses on the inter- and intra-dialectal variation attested within the Spanish language, heretofore exempted from the scrutiny that has characterized syntactic studies of other Romance languages. The analysis of said variability, which centers on the licensing of null and overt subjects, reveals intralingual differences that serve to bolster syntactic-theoretical argumentation and corroborate the structures and principles of the Minimalist Program.